2020
DOI: 10.1088/1748-9326/abaf85
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced understanding of poleward migration of tropical cyclone genesis

Abstract: The known trends of poleward migration for the tropical cyclone (TC) genesis in both hemispheres are discussed from different perspectives. It is shown that the poleward migration rate of the annually averaged latitude of TC genesis in the Northern Hemisphere is significantly affected by the regional variations of TC number in recent decades, especially an increase in the North Atlantic Ocean and a decrease in the western North Pacific Ocean. The poleward migration rates of TC genesis in the two hemispheres ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Previous studies have a consensus that TC latitudes (including latitudes of TC's lifetime‐maximum intensity and genesis) are poleward expansion (Altman et al., 2018; Daloz & Camargo, 2018; Kossin et al., 2014; Shan & Yu, 2020; Sharmila & Walsh, 2018; Studholme et al., 2022). For example, Kossin et al.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have a consensus that TC latitudes (including latitudes of TC's lifetime‐maximum intensity and genesis) are poleward expansion (Altman et al., 2018; Daloz & Camargo, 2018; Kossin et al., 2014; Shan & Yu, 2020; Sharmila & Walsh, 2018; Studholme et al., 2022). For example, Kossin et al.…”
Section: Resultsmentioning
confidence: 99%
“…Observations show that the LMI locations are southeast of the mean location, which may be related to the TCF locations (Studholme and Gulev 2018;Shan and Yu 2020;Lv et al 2022).…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies by Shan and Yu (2020, 2021) pointed out that the La Niña‐like pattern could influence TC occurrence frequency over the low latitude through modulating the large‐scale dynamical environmental conditions like relative vorticity and vertical wind shear by changing the zonal Walker circulation, which leads to increasing landfall TCs in southeastern China in recent decades. It is also possible that the thermodynamic effect of the SST may play an equivalently important role as that of the circulation change.…”
Section: Resultsmentioning
confidence: 99%
“…(2014), on the other hand, mentioned the influence of the interbasin TC frequency, but they found that the intrabasin rather than interbasin changes dominate the trend. Shan and Yu (2020) also quantified the effect of interbasin changes in TC frequency on the poleward migration of LMI. Although the interbasin changes in TC genesis frequency could influence the poleward migration of hemispheric mean LMI (or genesis) position, but could not be the cause of the poleward migration within one single basin.…”
Section: Introductionmentioning
confidence: 99%